2021
DOI: 10.3390/toxics9040088
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Human Health Risk Assessment of Pharmaceuticals and Hormones in Drinking Water Sources in the Metropolitan Area of Turin in Italy

Abstract: Pharmaceuticals and hormones (PhACs) enter the aquatic environment in multiple ways, posing potential adverse effects on non-target organisms. They have been widely detected in drinking water sources, challenging water companies to reassure good quality drinking water. The aim of this study was to evaluate the concentration of sixteen PhACs in both raw and treated drinking water sources in the Metropolitan Area of Turin—where Società Metropolitana Acque Torino (SMAT) is the company in charge of the water cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
(82 reference statements)
2
9
0
Order By: Relevance
“…Scientifically, it has been demonstrated that most conventional drinking water and waste water treatment plants are inefficient in treating PXCs [ 70 , 71 ] and usually the effluents of WWTP may end-up contaminating surface water which serve as source water for drinking water treatment plants. Thus, the occurrence of PXCs at significant levels in drinking water produced from conventional treatment plants [ 70 , 72 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientifically, it has been demonstrated that most conventional drinking water and waste water treatment plants are inefficient in treating PXCs [ 70 , 71 ] and usually the effluents of WWTP may end-up contaminating surface water which serve as source water for drinking water treatment plants. Thus, the occurrence of PXCs at significant levels in drinking water produced from conventional treatment plants [ 70 , 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scientifically, it has been demonstrated that most conventional drinking water and waste water treatment plants are inefficient in treating PXCs [ 70 , 71 ] and usually the effluents of WWTP may end-up contaminating surface water which serve as source water for drinking water treatment plants. Thus, the occurrence of PXCs at significant levels in drinking water produced from conventional treatment plants [ 70 , 72 ]. Papagiannaki et al [ 70 ] and Chen et al [ 73 ] partly attributed the removal inefficiency to the high (>3) of most PXCs and recommended the use of advanced treatment technologies to complement the conventional processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, several studies have evaluated the occurrence, effects, and risks of pharmaceutical compounds in the environment [ 1 , 2 , 3 , 4 ], with most of those studies concluding that pharmaceuticals can compromise water quality. The release of pharmaceuticals in effluents from manufacturing plants, hospitals, private households, as well as the inappropriate disposal of leftover medications, can contaminate surface water, ground water, and, eventually, drinking water [ 5 ]. Pharmaceuticals are commonly found in aquatic compartments at very low concentrations ranging from ultratrace (ng L −1 ) to trace (µg L −1 ) levels, which are currently regarded as potential hazard for a variety of living organisms, including humans [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used analytical techniques to determine trace levels of pharmaceuticals in water are high performance liquid chromatography coupled with ultraviolet detection (HPLC-UV) [ 51 ] or mass spectrometry (HPLC-MS) [ 5 ], as well as gas chromatography-mass spectrometry (GC-MS) [ 52 ]. Due to the polar, non-volatile, and thermally unstable nature of pharmaceuticals, LC-MS and LC-MS/MS are frequently used to analyze them in aqueous samples [ 46 ].…”
Section: Introductionmentioning
confidence: 99%